Perspectives of electric supply of municipal housing consumers in cities of Uzbekistan - A.G.Saidkhodjaev,Yu Bobojonov, U M Turdiev (International Journal of Advanced Science and Technology, 2020)
The article discusses the main prospects for the development of electricity supply for household consumers in the cities of the Republic of Uzbekistan. To solve the increased requirements for the reliability of power supply, it is proposed to use complex-connected electric networks, the introduction of automation and digital energy, an automatic system of commercial energy metering (ASCEM), as well as the use of reactive power compensation in urban electric networks.